Persistent Bronchopneumonia in an 8-Month-Old with Down Syndrome and Congenital Heart Disease: A Case Report - Mochamad Fauzan Dava; Shinta Nareswari (CV. Jasa Sukses Abadi, 2026)
Children with Down syndrome (DS) are at high risk of persistent pneumonia due to anatomical abnormalities of the airways, ciliary dysfunction, immune dysregulation, congenital heart disease (CHD), malnutrition, and aspiration. This case report describes the diagnostic approach and management of persistent bronchopneumonia in a DS infant with CHD and malnutrition. An 8-month-23-day-old female with DS, a history of anal atresia after anorectoplasty, presented with a 3-day history of severe, productive cough with phlegm, accompanied by fever, tachypnea (52 breaths/minute), chest wall indrawing, and bilateral moist rales. Nutritional status: W/A and W/H < p5 (malnutrition), microcephaly. Chest X-ray showed bilateral infiltrates. Blood gas analysis showed metabolic acidosis and hypoxemia. Sputum culture showed the growth of Enterococcus faecium resistant to ampicillin. Echocardiography showed secundum ASD and PDA (0.1–0.2 cm) with a left-to-right shunt. The patient was treated with oxygen, vancomycin, gentamicin, nebulizer, furosemide, captopril, and chest physiotherapy. Fever normalized on day 1, oxygen saturation normalized on day 4, and the cough persisted until day 6. The patient was discharged on day 7 with a catch-up immunization plan, aspiration education, and referral to cardiology and a nutrition clinic. This case highlights the need for early aspiration detection, sensitivity-guided antibiotics, and multidisciplinary care to prevent recurrence and improve quality of life.